Elevated alanine aminotransferase and low aspartate aminotransferase/alanine aminotransferase ratio are associated with chronic kidney disease among middle-aged women: a cross-sectional study - Hirotaka Ochiai (BMC Nephrology, 2020)
Abstract Background Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) to ALT ratio (AST/ALT ratio) have been shown to be related to non-alcoholic fatty liver disease or insulin resistance, which was associated with chronic kidney disease (CKD). However, it is unclear whether ALT and AST/ALT ratio are associated with CKD. In this study, we examined the relationship of ALT and AST/ALT ratio to CKD among middle-aged females in Japan. Methods The present study included 29,133 women aged 40 to 64 years who had an annual health checkup in Japan during April 2013 to March 2014. Venous blood samples were collected to measure ALT, AST, gamma-glutamyltransferase (GGT), and creatinine levels. In accordance with previous studies, ALT > 40 U/L and GGT > 50 U/L were determined as elevated, AST/ALT ratio < 1 was regarded as low, and CKD was defined as estimated glomerular filtration rate < 60 mL/min/1.73 m2 and/or proteinuria. Logistic regression model was used to calculate the odds ratio (OR) and 95% confidence interval (CI) for CKD. Results “Elevated ALT and elevated GGT” and “elevated ALT and non-elevated GGT” significantly increased the OR for CKD when compared with “non-elevated ALT and non-elevated GGT” (OR: 2.56, 95% CI: 2.10–3.12 and OR: 2.24, 95% CI: 1.81–2.77). Compared with “AST/ALT ratio ≥ 1 and non-elevated GGT”, “AST/ALT ratio < 1 and elevated GGT” and “AST/ALT ratio < 1 and non-elevated GGT” significantly increased the OR for CKD (OR: 2.73, 95% CI: 2.36–3.15 and OR: 1.68, 95% CI: 1.52–1.87). These findings still remained after adjustment for confounders. Conclusions Elevated ALT was associated with CKD regardless of GGT elevation. Moreover, low AST/ALT ratio was also associated with CKD independent of GGT elevation.